Climatizzazione della sicurezza: il caso delle migrazioni climatiche nelle agende di Stati Uniti e Australia (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
Today, the natural, social and political effects of the “climate crisis” are intensifying, bringing back the debate on the relationship between non-traditional phenomena, national security and democracy. Indeed, it is widely perceived that the involvement of traditional security actors (the executive branch, the military, government professionals) into non-traditional phenomena, such as climate migrations, can have severe effects on democratic values, as explained by studies on securitization (and its variations) and militarization. Mostly from a perspective of “practical geopolitics”, this article argues that climatization can help build a comprehensive adaptation to climate change effects, avoiding single target emergencies characterized by existential threats and military response, as demonstrated by the evolving case of the United States (where climatization has been recently launched) and Australia (where, in the absence of a political debate on climate security, climate migrations are evidently handled in undemocratic ways).
Keywords: Climate change; Climate crisis; Security; Migrations